Using costing technology based on time-driven jobs to reduce costs: an applied study in the General Company for Textile Industries in Hilla - Najaf Men’s Clothing Factory - Mahdi Al-Kawaz, Salah; Abdul Karim Al Baldawi, Shaker (Iraqi Journal for Administrative Sciences, 2024)
The time driven-functions based technique is regarded as the most important modern techniques in the field of the cost and managerial accounting that in its application can economic units achieve the objective of adding value to the customer by providing products matched its functional performance with customer requirements and a low prices and high quality as wall as the possibility of using the Quality Function Deployment technique as a methodology supportive to the technique above. Thus, the present research aims to study the two techniques above through the application in one of the State Company Factories for Textile Industries in Hilla that is the Najaf Factory for men clothes. To achieve this goal, the researcher was relied to apply the time driven- functions based costing technique on data that obtained through the medan cohabiting, while relied when the quality function deployment technique is applied on the questionnaire in order to inductive the views of customers who are dealing with the factory. The research was reached among the most important conclusions of the Najaf Factory for men clothes as a sample to the research suffers from lack of any features for the application of time driven-functions based costing technique that with its application can economic units achieve the goal of adding value to the customer as well as the lack of impact of the application of the quality function deployment technique as a methodology supportive of this technique, so the most importance recommendations that the research reached it is to devote the sufficient attention to apply the two techniques above to its role in achieving this goal.